Effect of extracellular products of Tenacibaculum maritimum in Atlantic salmon, Salmo salar L - R van Gelderen; J Carson; Barbara Nowak (2009)
Keywords: Atlantic salmon, extracellular products, LD50, Tenacibaculum maritimum, toxins. Tenacibaculum maritimum (formerly Flexibacter maritimus) is a well-known pathogen in a number of cultured fish species worldwide (Wakabayashi, Hikida & Masumura 1986; Alsina & Blanch 1993; Chen, Henry-Ford & Groff 1995; Handlinger, Soltani & Percival 1997; Ostland, LaTrace, Morrison & Ferguson 1999). It is a marine bacterium that causes necrotic lesions on the body, head, fins and gills, with erosive lesions on the external surface as the prominent clinical sign (Carson, McCosh & Schmidtke 1992). In Australia, the main species affected are Atlantic salmon, Salmo salar L., and rainbow trout, Oncorhynchus mykiss (Walbaum), in sea-cage culture in Tasmania (Handlinger et al. 1997). Experimental investigation into the pathogenesis of T. maritimum showed that challenge at higher doses (c. 1 · 108 cells mL)1) had an acute lethal effect on Atlantic salmon (van Gelderen 2007). Mortalities occurred within days and the clinical sign was the disintegration of the epithelium. In addition, a lack of an inflammatory response is characteristic of early flexibacteriosis lesions. Handlinger et al. (1997) suggested that this was the result of powerful exotoxins that prevent a host response. These findings pointed to a possible role of toxins in the pathogenicity of T. maritimum in Atlantic salmon. Effects of T. maritimum toxins have been explored in red and black sea bream, Pagrus major (Temminck and Schlegel), and Acanthopagrus schlegeli (Bleeker) (Baxa, Kawai & Kusuda 1988). In both fish species, extracellular products (ECP) showed insignificant in vitro activity; however, this did not correspond with the toxic effects observed in vivo with ECP recording the lowest LD50. Baxa et al. (1988) did indicate that the pathogenicity of T. maritimum in black and red sea bream may be ascribed in part to ECP. The current study investigated ECP toxicity in vivo to observe direct effects rather than in vitro activity of ...